Association between COVID-19 anxiety and temporomandibular disorders among dental students - an institutional survey - Safi, Sanna; Manzoor, Saima; Ullah, Fahim; Sardar, Tariq; Nasir, Umar; Mansoor, Nadia (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Objective The objective of this study was to find association between COVID-19 anxiety and temporomandibular disorders among dental students in an institutional survey. Methodology This descriptive cross-sectional study was conducted on undergraduate and postgraduate students of Khyber college of Dentistry, Peshawar from August to November 2021. Exclusion criteria was psychological disorders like anxiety, depression; anti-anxiety and anti-depressant medication; house officers and faculty. Data was collected on a questionnaire which consisted of Fonseca anamnestic index (IAF) to diagnose TMD, Hospital anxiety depression scale (HADS) to assess anxiety, depression and COVID-19 anxiety scale (CAS) to evaluate COVID-19 related anxiety. For data analysis, ean ± SD was used for age. Frequency and percentages were done for gender, TMD, anxiety, depression and COVID-19 anxiety. For association between categorical variables, chi-square was applied. Cross-tabulation and prevalence formula were used to find out prevalence of anxiety, depression and COVID-19 anxiety in TMD & non-TMD cases. Results A total of 181 students participated in this study. Out of this, 83(45.9%) were males and 98(54.1%) were females with a mean age of 22.7 ± 2.4 years. 99 (54.7%) were TMD cases i.e., greater than non-TMD cases (45.3 %). A higher trend of anxiety (78%) and depression (56%) was seen. Out of 99 (54.7%) TMD cases, 73 (73.7%) were with anxiety. But anxiety was even greater (n=69, 84.1%) in non-TMD cases. Depression was also almost equal in both TMD and non-TMD cases with a prevalence of 1.09. COVID-19 anxiety was seen in very few (1.1%). No association of TMD was seen with anxiety, depression and COVID-19 anxiety (p value ˃ 0.05). Conclusion There was no significant association found between COVID-19 anxiety and temporomandibular disorders in dental students of this study, with a very less prevalence of COVID-19 anxiety among them.